Association between DNA hypomethylation at IL13 gene and allergic rhinitis in house dust mite‐sensitized subjects. Issue 2 (February 2016) - Li, J.Y.; Zhang, Y.; Lin, X.P.; Ruan, Y.; Wang, Y.; Wang, C.S.; Zhang, L.
Summary: Background: Allergic rhinitis (AR) is a complex disease, in which gene–environment interactions contribute to its pathogenesis. Epigenetic modifications such as DNA methylation play an important role in the regulation of gene function. As IL13, a pleiotropic cytokine, may be important in conferring susceptibility to AR, the aim of the present work was to assess the relationship between a CpG island methylation status at the upstream of IL13 gene and house dust mite (HDM)‐sensitized AR in Han Chinese subjects. Methods: A total of 60 patients with HDM‐sensitized AR and 65 control subjects were enrolled as two independent cohorts from Beijing and Liaoning. MassARRAY EpiTYPER and pyrosequencing was used to systematically screen the status of DNA methylation in peripheral blood leucocytes. IL13 mRNA expression was measured by real‐time quantitative PCR. Electrophoretic mobility shift assay was used to assess the function of methylation site. Results: The mean level of methylation was decreased in the AR patient group compared with the control group ( P = 0.01). Two of a total of 33 IL13 CpG units analysed (CpG units 24 : 25 : 26 and 38 : 39) showed significant differences in methylation status between the AR patient group and the control group, with DNA hypomethylation at CpG38 significantly associated with higher risk of HDM‐sensitized AR in both independent cohorts and a combined cohort (Beijing: OR = 1.24, 95%CI = 1.01–1.52, P = 0.036; Liaoning: OR = 1.62, 95%CI = 1.11–2.38, P = 0.013; Combined: OR = 1.31, 95%CI = 1.10–1.56, P = 0.002). Methylation level of CpG38 correlated negatively with both IL13 mRNA expression and serum total IgE level and affected the binding affinity of SP1. Conclusions: DNA hypomethylation of IL13 gene may be associated with increased risk of AR from HDM sensitization.